MOLECULAR PHYLOGENY of THE GENUS KUMANOA (BATRACHOSPERMALES, RHODOPHYTA) - Vis, Morgan L.; Necchi, Orlando [UNESP]; Chiasson, Wayne B.; Entwisle, Timothy J. (Wiley-Blackwell, 2012)
Species belonging to the newly established genus Kumanoa were sampled from locations worldwide. DNA sequence data from the rbcL gene, cox1 barcode region, and universal plastid amplicon (UPA) were collected. The new sequence data for the rbcL were combined with the extensive batrachospermalean rbcL data available in GenBank. Single gene rbcL results showed the genus Kumanoa to be a well-supported clade, and there was high statistical support for many of the terminal nodes. However, with this gene alone, there was very little support for any of the internal nodes. Analysis of the concatenated data set (rbcL, cox1, and UPA) provided higher statistical support across the tree. The taxa K. vittata and K. amazonensis formed a basal grade, and both were on relatively long branches. Three new species are proposed, K. holtonii, K. gudjewga, and K. novaecaledonensis; K. procarpa var. americana is raised to species level. In addition, the synonymy of K. capensis and K. breviarticulata is proposed, with K. capensis having precedence. Five new combinations are made, bringing the total number of accepted species in Kumanoa to 31. The phylogenetic analyses did not reveal any interpretable biogeographic patterns within the genus (e.g., K. spermatiophora from the tropical oceanic island Maui, Hawaii, was sister to K. faroensis from temperate midcontinental Ohio in North America). Previously hypothesized relationships among groups of species were not substantiated in the phylogenetic analyses, and no intrageneric classification is recommended based on current knowledge.
Keywords: freshwater red algae; K; americana; K; holtonii; K; gudjewga; K; novaecaledonensis; systematics; taxonomy